지속가능 이동수단으로서의 자전거를 통해 본 공공디자인 인식증진 교육효과 - 이연숙(Yeun-Sook Lee); 이지연(Ji-Yeun Lee); 장유진(Yu-Jin Jang); 이윤이(Ryun-Yi Lee); 이명아(Myung-A Lee) (KIEAE Journal, 2024)
Purpose: Recently, Korea became the first country in the world to enact the Public Design Promotion Act and is seeking to increase national awareness of public design. The concept and range of public design have expanded to include social functions addressing problems caused by rapid urban development. Accordingly educational contents to empower to understand and participate in this trend is unavoidable. The purpose of this study was to develop an educational module on how bicycles and public design are interlinked for symbiosis with the nature ecosystem and to prove its learning effectiveness. Method: This study was conducted using a pre-post field experiment design. The module, developed starting in February 2023 and implemented in October, was designed to measure awareness of public design.The dependent variable of this study is the change in perception of public design through the lens of bicycles. Specifically, it includes the impact of bicycles on the ecosystem, awareness of the scope and value of public design, and changes in perception regarding urban environment development. Result: After the education, there was an increase in awareness of the impact of bicycles as a sustainable means of transportation and the scope and value of public design, which stimulated ideas for urban environment planning. This demonstrated that bicycles can develop within the multifaceted system of public design and contribute to solving social problems simultaneously. It also enhanced the awareness about the scope and value of public design, while helping to narrow the gap in ecological citizenship. KCI Citation Count: 0